PERAN KARYAWAN FRONT OFFICE TERHADAP CUSTOMER ENGAGEMENT NASABAH BANK MUAMALAT KOTA MAKASSAR - Nidar, Hasnidar Asni; Jusri, Jusri Jusri (Patria Artha University, 2019)
The high level of banking competition is no longer focused on consumer transactional behavior (repurchasing and cross-selling) but incorporates non-transactional behavior (word of mouth, blogging, co-creation). This study aims to determine the importance of the role of attitude of the employee on customer engagement. The location of this study was at Bank Muamalat Makassar with 70 customer samples, using the Smart PLS3 method. The results of this study indicate that attitude of the employee has a significant effect on customer satisfaction and customer engagement. Customer satisfaction has a significant effect on customer engagement. The contribution of this research is the presence of front office employee roles towards customer engagement.